Metal-Free Synthesis of Biaryl- and Teraryl-Cored Diarylmethanes by Ring Transformation of 2H-Pyran-2-ones - Singh, Fateh V.; Kole, Priyanka B. (Synthesis, 2019)
An efficient metal-free approach for the synthesis of functionalized biaryl-cored diarylmethanes is described by the ring transformation of 2H-pyran-2-ones using 4-phenylbutan-2-one as carbanion source. Moreover, 2H-pyran-2-ones were reacted with 1,3-diphenylacetone in the presence of base to achieve functionalized teraryl-cored diarylmethanes. All the ring transformation reactions were performed under mild reaction conditions to afford the biaryl- and teraryl-cored reaction products in high yields.
Keywords: biaryl-cored diarylmethanes; teraryl-cored diarylmethanes; 2H-pyran-2-ones; carbanion; ring transformation reactions; 4-phenylbutan-2-one; 1,3-diphenylacetone